DAMPAK NEPOTISME TERHADAP MOTIVASI KARYAWAN: SYSTEMATIC LITERATURE REVIEW - Najmi Azka Kamila; Isaura Rachma Agustin; Lilia Nasywa Zuhairina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Nepotism is a common occurrence in the workplace. Although the impact of nepotism on workplace commitment has been studied generally, studies specifically linking nepotism to employee motivational dimensions are still limited and in-depth. To address this gap, this literature review study was designed to examine the impact of nepotism on employee motivation. The research method used was a systematic literature review (SLR), conducted through the formation of a PICO, and using PRISMA 2020 to search and filter literature according to the inclusion criteria. This study found that nepotism is seen as a real threat to the stability and sustainability of organizations in the long term and has an impact on decreasing employee motivation, job satisfaction, and overall productivity. Equal opportunities for all employees in training, promotion, and career development are needed to minimize inequality caused by nepotism.